ETD: "We still have to unlearn. We are programmed, you know? analyzing black South African's violence against foreign black Africans Previous title: race and the "infernal circle" of dehumanization: an analysis of South Africa's negrophobia - Ndedi, Essombe Christiane (Department of Psychology, 2025)
In South Africa, “xenophobia” – the label commonly used to refer to Black South Africans' violence against foreign Black Africans - is often primarily connected to economic competition, which might silence any racial dynamics at play. Yet, given how western colonialism and White supremacy have shaped South Africa's trajectory, exploring the role that racial identities and racial relations play in Black South Africans' violence against foreign Black Africans, is relevant. To do so, I mobilized a decolonial qualitative approach that I conceptualized as a two-fold process aiming at: 1. assessing whether the colonial past remains present and 2. highlighting possible paths to interrupt such cycles at the individual and collective levels. Accordingly, on the theoretical front, I first provided an overview of dynamics associated with western colonialism's racist violence, namely identity erosion and the confinement into colonial archetypes, narcissism, and trauma bonds. I then focused on racist colonial violence in South Africa and also identified narcissism, identity erosion and trauma bonds as central dynamics along nationalism. Methodologically, I approached the decolonial aspirations of this study as requiring the positioning of Africa and Africans as privileged vantage points. I consequently centered orality as an epistemology and spoke over the phone with 79 Black Africans in South Africa (three citizens and 76 foreign nationals) who shared stories about racial identities and racial relations among Black Africans, including Black South Africans' relationship with foreign Black Africans. My decolonial intersectional narrative analysis of these stories suggested that Black Africans' contemporary racial identities might still be informed by colonial identity erosion, i.e., the confining of Black Africans into the colonial archetype of the deficient Black Other eligible for racist, capitalistic, and gendered colonial violence. As for racial relations between Black Africans, I suggested that they might be informed by colonial identity erosion, narcissism, trauma bonds and indirect rule. In participants' stories, resistance to such dynamics manifested whenever protagonists rejected the colonial archetype of the deficient Black Other – whether applied to themselves or the person they assisted – and refused to banalize violence against Black Africans. This study thus contributed to drawing attention to the violent and long-lasting psychological impacts of western colonialism along paths to interrupt such coloniality, namely by reclaiming identities that challenge colonial ideals.